The host galaxies of long-duration gamma-ray bursts in a cosmological hierarchical scenario - Nuza, Sebastian Ernesto (2007)
We developed a Monte Carlo code to generate long-duration gamma-ray burst (LGRB) events within cosmological hydrodynamical simulations consistent with the concordance Λ cold dark matter model. As structure is assembled, LGRBs are generated in the substructure that formed galaxies today. We adopted the collapsar model so that LGRBs are produced by single, massive stars at the final stage of their evolution. We found that the observed properties of the LGRB host galaxies (HGs) are reproduced if LGRBs are also required to be generated by low-metallicity stars. The low-metallicity condition imposed on the progenitor stars of LGRBs selects a sample of HGs with mean gas abundances of 12 + log O/H ~ 8.6. For z < 1 the simulated HGs of low-metallicity LGRB progenitors tend to be faint, slow rotators with high star formation efficiency, compared with the general galaxy population, in agreement with observations. At higher redshift, our results suggest that larger systems with high star formation activity could also contribute to the generation of LGRBs from low-metallicity progenitors since the fraction of low-metallicity gas available for star formation increases for all systems with look-back time. Under the hypothesis of our LGRB model, our results support the claim that LGRBs could be unbiased tracers of star formation at high redshifts.